Stocks of Admired and Spurned Companies - Anginer, Deniz (2012)
Do stocks of admired companies yield admirable returns? Are increases in admiration followed by high stock returns, and how reliable is the relation between admiration and returns? These questions are answered by the authors based on their study of Fortune magazine's annual list "America's Most Admired Companies." They find that from April 1983 through December 2007 stocks of admired companies had lower returns, on average, than stocks of spurned companies and that increases in admiration were followed, on average, by lower returns. The authors also find that the dispersion of returns is high, especially in the portfolio of spurned company stocks, implying that investors who would like to benefit from the return advantage of spurned company stocks must diversify widely among them.